Knowledge acquisition toward startups' perspectives: Empirical cross-case study of leading technology business incubators in Thailand - Kittichai Rajchamaha (2019)
© 2018 Universiti Putra Malaysia Press. Startup progress is recognized as a vital driver to sustain economies. A technology business incubator (TBI) is one of the devices to serve it. Recent studies have found that one of the TBI's key success factors in assisting startups' survival is knowledge management (KM), particularly knowledge acquisition (KA). This study aims to examine startups' behaviors toward their KA that occurred between before and after accessing early-stage incubation (ESI) of TBIs. The study used a qualitative case survey research (Yin, 2013) for five selected cases of leading TBIs in Thailand, namely PSU, KKU, SUT, NSTDA, and STEP. Purposive sampling was used with data gathered from a total of 114 startups who were incubated from 2014 to 2016. Data were collected using primary data through a survey method with semi-structured questionnaires. A summative content analysis, validity, and reliability were used and tested. A conceptual model was created from reviewing recent studies and theories, including resource-based view, knowledge-based view, and KA theories to explore purposes. Findings show that startups' behaviors toward KA before accessing ESI need to acquire technical knowledge through online channels using "search engines" and "target websites" with more frequencies of KA. Startups' demand toward KA after accessing ESI is the need to acquire business rather than technical knowledge through both offline and online channels regarding methods related to different knowledge sources with more frequency. This shows both academic and practical contributions conducted at leading TBIs.